A STUDY OF TEACHING COMPETENCY AMONG SCHEDULED CASTE AND NON-SCHEDULED CASTE PUPIL TEACHERS IN RELATION TO THEIR EMOTIONAL INTELLIGENCE (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The present study aims to assess and compare and relate the Emotional Intelligence with the Teaching Competency of teacher trainees. For this purpose 400 teacher trainees were selected from various educational institutions Panjab University. The data was again divided into Schedule Caste and Non-Schedule Caste category. For statistical analysis, mean, S. D., t test and Correlation of Coefficient were worked out. The results showed that there was no significant difference between Schedule Caste and Non-Schedule Caste teacher trainees on the variable of Emotional Intelligence. Whereas regarding Teaching Competency, there was no significant difference between Sc and Non-Sc teacher trainees.